Laser, buffer layer and CoCrPtOx-assisted low temperature fabrication process of a small-sized-CNT pattern by MPCVD - Teng, I-Ju; Hong, Tsai-Hau; Hsu, Hui-Lin; Jian, Sheng-Rui; Wang, Wei-Hsiang; Kuo, Cheng-Tzu (My University, 2010)
For improving compatibility with IC processes, this work presents a low temperature process (<400 degrees C) to fabricate a small-sized-carbon nanotube (CNT) (<6 graphene layers) pattern by buffer layer (AlN) and CoCrPtOx catalyst precursor-assisted microwave plasma chemical vapor deposition (MPCVD). Without high temperature heating on the whole specimen, the low temperature process mainly results from selective local activation laser heating (>= 600 degrees C) to form the catalyst nanostructures, which are beneficial to low temperature H-plasma treatment to form catalyst nanoparticles for CNT growth. The functions of the buffer layer and the catalyst precursor are to help the heat dissipation and the small-sized CNT formation. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Small-sized-CNT pattern; Buffer layer; CoCrPtOx catalyst precursor; Microwave plasma chemical vapor deposition (MPCVD); Selective local laser heating